Pemahaman Hadis-Hadis Tentang Lingkungan: Studi Kasus Kerusakan Mangrove di Pantai Cermin Kabupaten Serdang Bedagai - Rahayu, Sri Ulfa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was carried out because the mangrove protection debt in Pantai Cermin District, Serdang Bedagai Regency was already denuded, causing damage to the ecosystem. This makes researchers want to look for hadiths about the environment. The aim of the research is to understand hadiths about the environment, various functions of mangroves, and symptoms caused by environmental damage. The research method used in this research is a qualitative method through a revelation approach, namely by studying Islamic literature sourced from the Koran and Hadith. The result is that there are several verses in the Koran that contain environmental issues, namely surah al-A'raf 56, 74, al-Baqarah verses 11,12,30, 60, al-Qasas 77, ar-Rum 41, and Yunus verse 41. There are many hadiths related to the environment, namely planting trees and reforestation, reviving dead land, air, water, maintaining the balance of nature.